Late payment issues of subcontractors in Malaysian construction industry - Che Haron, Roziha; Arazmi, Ahmad Lutfil (Malaysian Institute Of Planners, 2020)
The practice of efficient and timely payment in construction projects is a major factor that can contribute to the success of a project. Delays in payment to subcontractor(s) by main contractor and client on construction projects in the Malaysian construction industry is considered to be a significant factor of concern. It causes severe cash flow problems to subcontractor(s) and this condition may lead to a devastating impact to the contractual payment chain. Withholding or delaying payment creates financial hardship for the construction companies and its impacts are sometimes so harsh that some companies have to close down their services. The research methodology adopted was the questionnaire survey analysis based on thirty (37) respondents from selected main contractors and sub-contractors in Gombak, Selangor. The data and information were also gathered from interviews analysis. From the research findings, among the factor of late payment from the client is payment withhold by the client. Meanwhile, the factor of late payment from the main contractor is when the term of “pay when paid” is applied. To improve the payment situation, the findings of this study suggest that there must be dedicated enforcing provisions for payment delay in contracts. This is proposed by introducing the standard form of contract clause regarding payment between the main contractor and domestic subcontractor which include levying charges on overdue payments.